ANALISIS BEBAN KERJA PADA RECEPTIONIST SELAMA HIGH SEASON PACIFIC PALACE HOTEL BATAM - Prisila Natacia Suciadi; Okki Kurnia; Devid Trinaldo Simatupang; Nensi Lapotulo (Journal of Innovation Research and Knowledge, 2024)
During high season, hotels often experience high occupancy rates, which can lead to increased workload for hotel staff, including receptionists, housekeeping, and other services (Alrawabdeh, 2022). Receptionists play an important role as the spearhead in providing services to guests, from the check-in process, answering guest questions, to handling complaints. High workloads during high season often lead to decreased performance, work stress, and even potential errors in service (Sáez-Fernández, 2020). Based on the description above, researchers are interested in conducting a study entitled "Analysis of Receptionist Workload During the High Season of the Pacific Palace Hotel Batam" Causes of receptionist workload during the high season at the Pacific Palace Hotel The results of interviews, data collection through direct observation and documentation resulted in several discussions regarding the causes of receptionist workload during the high season at the Pacific Palace Hotel, there are 4 indicators of receptionist workload during the high season, namely the guest volume of more than 50 guests, while in the low season, only around 15-20 guests. Receptionist working hours increase significantly during high season, work difficulties are special requests, and urgent situations during high season make receptionist work much more complex and challenging, Psychological pressure of workload spikes during high season creates real psychological pressure for receptionists, which impacts their mental health and performance. Strategies or recommendations to manage receptionist workload to remain optimal during high season at Pacific Palace Hotel Batam are direct supervisor supervision to ensure excellent service